PSYCHOTHERAPEUTIC ASSISTANCE TO FAMILIES OF MILITARY PERSONNEL DURING WAR - Demydiuk, Volodymyr; Balashov, Eduard (Scientific Journal of Polonia University, 2023)
The purpose of the study is to determine the impact of systemic psychotherapy in working with military families. The methodology of studying emotional burnout by V. Boyko and the methodology of diagnosing mental states such as anxiety, frustration, aggression and rigidity by H. Eysenck were used in the empirical research. Pearson correlation coefficient was used for finding correlations between authoritarian hypersocialization and feelings of guilt, negativism, depression, anxiety, irritability among the military families. A comparative analysis of the emotional sphere indicators of military families raising children after psychological training in systemic psychotherapy revealed statistically significant differences in such indicators as guilt, irritability, suspicion, frustration, anxiety, depression, and significantly higher mood indicators. Thus, after undergoing psychological training in systemic psychotherapy, the families of servicemen and women experienced a decrease in guilt, irritability, suspicion, and frustration, and an increase in positive well-being and mood. It has been discovered that in military families, difficulties in relationships with children are associated with negativism, irritability, increased anxiety, rigidity, and emotional burnout. It has been proven that an increase in anxiety in military families increases the level of irritability, emotional burnout, and guilt.